Personality effective factors in reducing PTSD in earthquake in order to develop a structural model in Kermanshah city - Jahangiri, Susan; Delavar, Ali; Dortaj, Fariborz (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of determining the role of personality factors in predicting the symptoms of post-traumatic stress disorder in people exposed to trauma. Methods: The current research method was the type of correlation designs and structural equation modeling method. The statistical population in this research included all the earthquake victims of the recent Kermanshah earthquake, whose number is about 21,000 people. According to Morgan's table, 377 people were selected as simple random sampling. The data were obtained using the Mississippi PTSD citizenship scale (Kian et al., 1988) and the five-factor personality questionnaire (Costa & McCree, 1985). In order to describe the research variables, standard deviation, average, skewness and kurtosis indices were used. Frequency and percentage indicators were also reported for demographic characteristics. It should be mentioned that SPSS software was used for descriptive analysis. In the inferential part, in order to test the hypotheses of the research, modeling of structural equations with Amos software was used. Results: The results showed that the components of adaptability, conscientiousness and openness had a negative effect on PTSD, the relationship between adaptability and PTSD was directly equal (t=-3.97 and β=-0.18), the relationship of conscientiousness It is directly equal to PTSD (t=-3.84 and β=-0.17) and the relationship of openness with PTSD is directly equal to (t=-4.49 and β=-0.20). Also, the results show that the neuroticism component had a positive effect on PTSD, the relationship between neuroticism and PTSD is directly equal (t = 9.23, β = 0.41). Conclusion: It can be concluded that the results of the statistical test showed that the fit indices of the research model are in a favorable condition. Also, the components of adaptability, conscientiousness and openness have had a negative effect on PTSD, and the component of neuroticism has had a positive effect on PTSD.